(3GdefJbi ef JGQjN GdESdGe ddPgHis - (3CHh HcQ Hf CMeO Hf eMeO Hf YeQ GdCSOj GdTgHj GdOeTbqj, Jbqj GdOjf , (B851 (3g`s; (3GdPgHj,J (B748 (3g` s
(3ChdgG (B:s
(3hChd eG ajg jHOC ef CKfGA SfI (B418(3g` s
(3BNQgG (B:s
(3hjfJgi SfI (B470(3g` s
(3eLdO fGbU ef Chdg ebOGQ YTQ cQGQjSs
(3LRA ef GdeNWhW ecJhH HNW eNda dNW GdeDdas
(3hGdejcQhajde Hg Jda HSjWs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs